Annealing temperatures affect 16S rRNA gene-amplicon Illumina sequencingbased bacterial community analysis of canine skin - Apostolopoulos, N; Thom, N; Bagwe, R; Müller, RR; Ewers, C; Glaeser, PS (Journal of the Hellenic Veterinary Medical Society, 2023)
Analysis of the bacterial community structure of dog skin samples, sequencing the 16S rRNA gene is nowadays widely used. Among others, the 16S rRNA gene amplicon Illumina sequencing technique is well established and routinely applied to get a first inside into the bacterial community diversity and taxonomic composition. However, as it is a molecular-based technique, bias due to methodology is possible and should be minimized. In this study, we tested the effects of annealing temperature (50°C vs 55°C) on the 16S rRNA gene amplicon analysis of the bacterial microbiota of skin and ear canal samples from a German shepherd dog. Although beta diversity was not affected by the higher annealing temperature, alpha diversity values showed a shift (overall diversity (Shannon) and evenness were increased, whereas dominance (D), number of taxa (S), richness (Chao 1) and the total numbers of individuals (N) were reduced, with higher annealing temperature). The biological relevance of this finding remains unclear. Thus, our results underline the importance of optimal annealing temperature in order to minimize bias, as well as the necessity of further similar studies with a larger sample size.